2019
DOI: 10.1016/j.ijdevneu.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Neglect, HPA axis reactivity, and development

Abstract: Neglect is a common and frequently chronic form of child maltreatment that can compromise child development and increase the risk of physical and psychological problems. In this review, we discuss one of the potential ways neglect becomes biologically embedded by shaping the development of a key stress responsive system: namely, the hypothalamic‐pituitary‐adrenal (HPA) axis. Several potential mediators and moderators of this process are examined, including inflammation, attachment and social buffering, self‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 111 publications
(128 reference statements)
1
34
0
Order By: Relevance
“…Firstly, disorganization coincided with a flattened diurnal cortisol slope in infancy in the aforementioned Generation-R study, with follow-up analyses implicating a hypocortisolism that applied particularly to the disorganized children with an insecure rather than a secure secondary classification (113). Crucially, at the level of the HPA axis, large-scale studies have recently documented that maltreatment, in particular when occurring early and involving neglect by the caregiver, is linked with hypocortisolism (123)(124)(125)(126). This tamping down or "blunting" of indices composing the aversion module may reflect the long-term consequences of an "evolutionarily conservative" response involving an excessively self-reliant emotion regulation strategy that is metabolically less costly and minimizes the risk inherent in depending on others as sources of co-regulation (127,128).…”
Section: Alterations In the Aversion Modulementioning
confidence: 95%
“…Firstly, disorganization coincided with a flattened diurnal cortisol slope in infancy in the aforementioned Generation-R study, with follow-up analyses implicating a hypocortisolism that applied particularly to the disorganized children with an insecure rather than a secure secondary classification (113). Crucially, at the level of the HPA axis, large-scale studies have recently documented that maltreatment, in particular when occurring early and involving neglect by the caregiver, is linked with hypocortisolism (123)(124)(125)(126). This tamping down or "blunting" of indices composing the aversion module may reflect the long-term consequences of an "evolutionarily conservative" response involving an excessively self-reliant emotion regulation strategy that is metabolically less costly and minimizes the risk inherent in depending on others as sources of co-regulation (127,128).…”
Section: Alterations In the Aversion Modulementioning
confidence: 95%
“…Early-life adversity has strong influences on stress response system development in children (Koss & Gunnar, 2018; Reilly & Gunnar, 2019). A particularly extreme form of early adversity is deprivation of parental care associated with institutional rearing.…”
Section: Early Life Adversity and Stress Responsivenessmentioning
confidence: 99%
“…We did not assess during which developmental period maltreatment occurred. It has been suggested that neglect during the first two to three years of life is particularly crucial in programming HPA-axis functioning (37,98). Our assessment of maltreatment does not allow us to discern between neglect starting early in the development and neglect that occurred later in the development.…”
Section: Limitationsmentioning
confidence: 92%